COMPARISONING FACTORS IN DESIGN ACOUSTIC CLASSROOM IN INDONESIA - Hajizah Azmi Siregar (Journal of Architectural Research and Education, 2022)
This paper presents the Analytic Hierarchy Process (AHP) technique of decision making and elimination. Acoustics affect concentration, memory, and the comfort of learning and teaching. Research shows that the effectiveness of classroom acoustics can directly affect students' ability to concentrate. Students with low grades cannot focus when distracted, and students must catch 90% of the teacher's explanations in class. When teachers amplify their voices, it causes health problems. Acoustics in the classroom can improve concentration and comfort for both students and teachers. According to acoustic engineers, sound insulation and reverberation time are the most important factors in designing classroom acoustics. Reverberation time is the time it takes for the sound in a room to decay over a certain dynamic range. The sound insulation can help soundproof the insulating characteristics of the material increase with more mass. The lack of structural connections makes it soundproof. From an architect's point of view, reverberation time is slightly important. It is because many architecture students in Indonesia do not get much acoustic material in school. Their understanding of building acoustics is still lacking. Architecture students in Indonesia need more in-depth acoustic materials to be able to use their acoustic abilities professionally. According to architects and educators, speech intenbillity is the most important factor. From the three experts' points of view, the most important things when designing classroom acoustics are reverberation time, sound insulation, and speech intenbillity.Keywords: Analytic Hierarchy Process (AHP), Acoustic Classroom, Indonesia, Reverberation Time, Sound Insulation, and Speech intenbillity.